Pentoxifylline Attenuates Cardiac Remodeling Induced by Tobacco Smoke Exposure - Minicucci, Marcos [UNESP]; Oliveira, Fernando [UNESP]; Santos, Priscila [UNESP]; Polegato, Bertha [UNESP]; Roscani, Meliza [UNESP]; Fernandes, Ana Angelica [UNESP]; Lustosa, Beatriz [UNESP]; Paiva, Sergio [UNESP]; Zornoff, Leonardo [UNESP]; Azevedo, Paula [UNESP] (Arquivos Brasileiros Cardiologia, 2016)
Background: Tobacco smoke exposure is an important risk factor for cardiac remodeling. Under this condition, inflammation, oxidative stress, energy metabolism abnormalities, apoptosis, and hypertrophy are present. Pentoxifylline has anti-inflammatory, anti-apoptotic, anti-thrombotic and anti-proliferative properties. Objective: The present study tested the hypothesis that pentoxifylline would attenuate cardiac remodeling induced by smoking. Methods: Wistar rats were distributed in four groups: Control (C), Pentoxifylline (PX), Tobacco Smoke (TS), and PX-TS. After two months, echocardiography, invasive blood pressure measurement, biochemical, and histological studies were performed. The groups were compared by two-way ANOVA with a significance level of 5%. Results: TS increased left atrium diameter and area, which was attenuated by PX. In the isolated heart study, TS lowered the positive derivate (+dp/dt), and this was attenuated by PX. The antioxidants enzyme superoxide dismutase and glutathione peroxidase were decreased in the TS group; PX recovered these activities. TS increased lactate dehydrogenase (LDH) and decreased 3-hydroxyacyl Coenzyme A dehydrogenases (OH-DHA) and citrate synthase (CS). PX attenuated LDH, 3-OH-DHA and CS alterations in TS-PX group. TS increased IL-10, ICAM-1, and caspase-3. PX did not influence these variables. Conclusion: TS induced cardiac remodeling, associated with increased inflammation, oxidative stress, apoptosis, and changed energy metabolism. PX attenuated cardiac remodeling by reducing oxidative stress and improving cardiac bioenergetics, but did not act upon cardiac cytokines and apoptosis.
Keywords: Tobacco Smoke Pollution; Ventricular Remodeling; Pentoxifylline; Oxidative Stress; Cardiomyopathies